IC 6357 Methods And Costs Of Treatment At The Calumet & Hecla Reclamation Plant - C. Harry Benedict (The National Institute for Occupational Safety and Health (NIOSH), 1930)
This paper, describing the leaching practice at the Calumet and Hecla mills, Lake Linden, Mich., is one of a series on milling methods and costs being published by the United States Bureau of Mines. GENERAL DESCRIPTION The reclamation plant is located along the shores of Torch Lake at a slightly lower level than the concentrator itself. The entire location of the original concentrator, in connection with the present reclamation plant, has been ideal, lore particularly as the leaching and flotation departments are common to both units. After 15 years of operation and with the reclamation sands just a little more than half exhausted it would appear that the remaining life of the deposit could be worked by the present plan, without decided changes or renewals of plant or equipment.